2012
DOI: 10.1371/journal.pone.0040565
|View full text |Cite
|
Sign up to set email alerts
|

Ecdysone Induced Gene Expression Is Associated with Acetylation of Histone H3 Lysine 23 in Drosophila melanogaster

Abstract: Posttranslational modification of histones regulates transcription but the exact role that acetylation of specific lysine residues plays in biological processes in vivo is still not clearly understood. To assess the contribution of different histone modifications to transcriptional activation in vivo, we determined the acetylation patterns on the ecdysone induced Eip74EF and Eip75B genes in Drosophila melanogaster larvae by chromatin immunoprecipitation. We found that acetylation of histone H3 lysine 23 is loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 51 publications
1
23
1
1
Order By: Relevance
“…mori . Moreover, in D. melanogaster , H3K23 is one of the acetylation sites of DmCBP (Bodai et al ., ); however, BmCBP did not enhance H3K23 acetylation in this study (Fig. ), suggesting that CBP acetylation sites vary amongst insects.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…mori . Moreover, in D. melanogaster , H3K23 is one of the acetylation sites of DmCBP (Bodai et al ., ); however, BmCBP did not enhance H3K23 acetylation in this study (Fig. ), suggesting that CBP acetylation sites vary amongst insects.…”
Section: Discussioncontrasting
confidence: 61%
“…germanica metamorphosis (Fernandez-Nicolas and Belles, 2016). Drosophila CBP is also involved in establishing the DNA replication checkpoint during DNA synthesis (Blander et al, 2002;Pichierri and Franchitto, 2004;Smolik and Jones, 2007), and has been found to acetylate histone H3 lysine 23 and regulate the transcription of ecdysteroid pathway genes (Bodai et al, 2012). In Camponotus floridanus (Florida carpenter ant), CBP regulates foraging and scouting behaviours by catalysing histone acetylation (Simola et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Also, mammalian Moz targets H3K9 in vivo and regulates the expression of Hox genes, but the global H3K9Ac levels are not significantly affected in the homozygous Moz mutant (Voss et al 2009), indicating that other HATs have overlapping substrate specificity with Moz. In flies, a previous study had reported that the H3K23Ac levels were reduced 35% in nejire (nej) mutant embryos, which lack functional CBP/p300 (Bodai et al 2012). However, knocking down nej by dsRNA in S2 cells severely reduced levels of H3K27Ac but had no obvious effect on global levels of H3K23Ac (Tie et al 2009).…”
Section: Discussionmentioning
confidence: 95%
“…Another study showed that the plant homeodomain (PHD)-bromodomain of TRIM24, a coactivator for estrogen receptor a in humans, binds to unmodified H3K4 and acetylated H3K23 within the same H3 tail (Tsai et al 2010). Also, the levels of H3K23Ac at two ecdysone-inducible genes, Eip74EF and Eip75B, have been shown to correlate with the transcriptional activity of these two genes at the pupal stage, suggesting the involvement of H3K23Ac in ecdysone-induced transcriptional activation (Bodai et al 2012). In this study, we further provided evidence for the activating role of the Enok-mediated H3K23Ac mark in transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…FBgn0041092 Bai et al, 2000;Xie et al, 2015;Zhang et al, 2015 Interacts Zraly et al, 2006;Mazina et al, 2018 SWI/SNF Activation and repression of ecdysone-dependent genes Neiire (CBP/p300) FBgn0261617 Kirilly et al, 2011;Bodai et al, 2012;Mazina et al, 2018 Interacts with EcR in ecdysone-dependent way, promotes Histone H3 K27 acetylation at ecdysone-dependent genes, is important for ecdysone-dependent transcription activation…”
Section: Taimentioning
confidence: 99%